Mikrovlnný dělič z vlnovodu integrovaného v substrátu - Böhm, Patrik; Patrik Böhm (České vysoké učení technické v Praze, 2023)
Práce se zabývá stručným popisem a přehledem technologie vlnovodů integrovaných do substrátu, označované jako SIW. Je zde popsán princip funkce a vlastnosti obdélníkových vlnovodů, SIW a jeho modifikací (AFSIW, HMSIW). Následuje shrnutí základních druhů přechodů mezi SIW a planárními strukturami a ukázka modelů reálných aplikací SIW s jejich parametry. Práce končí popisem děličů výkonu realizovaných pomocí SIW a následným návrhem děliče výkonu se středem pásma na 7 GHz. Dělič je simulován, vyrobena poté změřen.

The work deals with a brief description and overview of the technology of waveguides integrated into the substrate, referred to as SIW. The principle of function and properties of rectangular waveguides, SIW and its modifications (AFSIW, HMSIW ) are described here. The following is a summary of the basic types of transitions between SIW and planar structures and a sample of models of real SIW applications with their parameters. The work ends with a description of power dividers implemented using SIW and the subsequent design of a power divider with the center of the band at 7 GHz. The divider is simulated, manufactured and then measured.
Substrate-Integrated-Waveguide Power Divider
Keywords: vlnovod; SIW; vedení; AFSIW; HMSIW; dělič výkonu; waveguide; SIW; transmission line; AFSIW; HMSIW; power divider